2017
DOI: 10.1089/ten.tec.2016.0377
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Adipose-Derived Stromal Vascular Fraction Cells Using a Novel Point-of-Care Device: Cell Characterization and Review of the Literature

Abstract: The GID SVF-1 and GID SVF-2 are closed-system, disposable, scalable cellular isolation devices designed for isolating the human adipose-derived stromal vascular fraction (hSVF) from lipoaspirates at the clinical point of care. The purpose of this study was to characterize the device performance with respect to cell yield and viability of the hSVF, as well as the hSVF purity and cellular composition. Our results demonstrate that adipose-derived hSVF can be safely obtained using both devices and standardized met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 56 publications
3
52
1
4
Order By: Relevance
“…This amount of SVF cells correlates to results from human studies in which the average SVF yield has been reported to range from 7.19 × 10 5 to 9.55 × 10 5 live cells/g adipose tissue. 32 34 In addition, similar to previous human studies, we demonstrated a significantly higher SVF yield from adipose tissue harvested by surgical excision compared with liposuction, 35 37 and a higher density of SVF cells in the lipoaspirate from the abdomen compared with the back. 35 , 38 , 39 …”
Section: Discussionsupporting
confidence: 88%
“…This amount of SVF cells correlates to results from human studies in which the average SVF yield has been reported to range from 7.19 × 10 5 to 9.55 × 10 5 live cells/g adipose tissue. 32 34 In addition, similar to previous human studies, we demonstrated a significantly higher SVF yield from adipose tissue harvested by surgical excision compared with liposuction, 35 37 and a higher density of SVF cells in the lipoaspirate from the abdomen compared with the back. 35 , 38 , 39 …”
Section: Discussionsupporting
confidence: 88%
“…Adipose tissue adult stem cells, termed stem cells or mesenchymal stem cells (MSCs), can be harvested through surgery and direct excision, liposuction in the trunk and extremities as well as the Coleman technique for fat tissue transplantation and remodelling. This technique has shown a higher yield of viable adipocytes than conventional liposuction [ 1 , 17 , 18 ]. In liposuction, the unwanted fat of a part of the body is removed by aspiration and injected in the areas where increased volume is required or to achieve a cosmetic improvement.…”
Section: Adipose Tissue Stem Cells In Regenerative Medicinementioning
confidence: 99%
“…Stem cells can be classified by their origin as: (a) embryonic; (b) fetal; (c) adult and (d) induced pluripotent. The classification can be simplified as embryonic and adult mesenchymal [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations